2020
DOI: 10.1590/1806-9282.66.9.1277
|View full text |Cite
|
Sign up to set email alerts
|

Discriminant indexes to simplify the differential diagnosis between iron deficiency anemia and thalassemia minor in individuals with microcytic anemia

Abstract: SUMMARY INTRODUCTION: Microcytic anemias are very common in clinical practice, with iron deficiency anemia (IDA) and thalassemia minor (TT) being the most prevalent. Diagnostic confirmation of these clinical entities requires tests involving iron metabolism profile, hemoglobin electrophoresis, and molecular analysis. In this context, several discriminant indices have been proposed to simplify the differential diagnosis between IDA and TM. OBJECTIVE: The aim of this paper was to demonstrate the clinical relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
(5 reference statements)
0
2
0
Order By: Relevance
“… 29 However, a review article showed that despite the excellent performances of the Green and King index (IGK), the Ehsani index, and RBC count, none of them presented sufficient sensitivity and specificity to establish a diagnosis between thalassemia and IDA, and these tests require more time-consuming and costly methods. 30 As mentioned earlier, there is a limitation in studies that investigate the prevalence of anaemia in Iraq; to the best of our knowledge, this is the first study to investigate this aspect among children in Karbala, Iraq. Our findings showed that the prevalence of anaemia among children aged 0–14 years in Karbala was 9.9%, which is considered high.…”
Section: Discussionmentioning
confidence: 84%
“… 29 However, a review article showed that despite the excellent performances of the Green and King index (IGK), the Ehsani index, and RBC count, none of them presented sufficient sensitivity and specificity to establish a diagnosis between thalassemia and IDA, and these tests require more time-consuming and costly methods. 30 As mentioned earlier, there is a limitation in studies that investigate the prevalence of anaemia in Iraq; to the best of our knowledge, this is the first study to investigate this aspect among children in Karbala, Iraq. Our findings showed that the prevalence of anaemia among children aged 0–14 years in Karbala was 9.9%, which is considered high.…”
Section: Discussionmentioning
confidence: 84%
“…North Waziristan has been divided into three subdivisions. Participants Criteria: All the confirmed thalassemia minor patients was included in this study confirmed by Hb electrophoresis and other then thalassemia minor was excluded 21 . Data Collection Procedure: To collect information from Thalassemia minor patients, a questionnaire was designed, pretested and finalized before the actual survey was conducted.…”
Section: Study Design and Settingmentioning
confidence: 99%